Development of Socialist Cooperativism in the Slovenian Part of Yugoslavia: Communist Authorities’ Attitude towards Peasants and Private Agriculture (1945−1970s) - Rendla, Marta (Historical Studies on Central Europe, 2025)
The article addresses the changing attitude of the communist authorities towards peasants and private agriculture in the Slovenian part of socialist Yugoslavia. The changing attitude towards peasants and private agriculture, through socialist cooperativism, was based on political, economic, and social discrimination against peasants. After years of intense political, economic, and psychological violence, a period of ideological pragmatism began following the abandonment of collectivization in 1953. The authorities sought to appease the peasants, allowing them to leave agricultural cooperatives without any consequences. Within the framework of socialist cooperation, peasants were permitted to pursue their economic interests, but they were obliged to further narrow production units to ten hectares of arable as a maximum land. In the 1960s, the authorities neglected peasants through the cooperative system, believing that large state agricultural complexes would ensure food security. When these complexes failed to meet the growing needs for food security, the importance of private agriculture was recognized at the brink of the 1970s. At that time, the authorities changed the concept of agricultural policy, allowing peasants to modernize and invest in the upgrading of private agriculture. The productive potential of private agriculture was also incorporated into the state agricultural policy plans, giving more room for private initiative. Despite their pragmatism, the authorities did not fully shed their ideological prejudices against peasants and private agriculture until the dissolution of socialism and the state.